Protein C Deficiency in a Patient of Acute Myocardial Infarction (Ibrahim Medical College Journal, 2009)
A 42-year old male presented with acute myocardial infarction with no discernable risk factors; he never smoked; did not suffer from diabetes and had a well controlled blood pressure with single medication; plasma concentration of total cholesterol was on the upper normal limit, high and low density lipoprotein, cholesterol and triglyceride being normal. In addition to a single antihypertensive he received Allupurinol (Xanthine Oxidase inhibitor) for hyperuricaemia. Coronary angiogram revealed ectatic epicardial coronary arteries. The patient developed deep vein thrombosis of right leg after four days of the coronary angiogram. Coagulation analysis revealed protein C deficiency. The recognition of protein C deficiency as a risk factor for myocardial infarction is important as anticoagulators prevent further thrombotic events whereas inhibitors of platelet aggregation are ineffective. Ibrahim Med. Coll. J. 2009; 3(1): 34-35 Key words: myocardial infarction, risk factors, protein C deficiency, anticoagulation.   doi: 10.3329/imcj.v3i1.2918